La verità, vi prego, sul criterio del creditore privato: Commissione c. FIH Holding e FIH Erhvervsbank - Rosanò, Alessandro (European papers (Online. periodico), 2019)
In Commission v. FIH Holding and FIH Erhvervsbank (judgement of 6 March 2018, case C-579/16 P), the Court of Justice dealt with the case of a bank, beneficiary of an aid scheme, that had already been granted a number of benefits, which were approved by the European Commission as aid schemes compatible with the internal market. The Court held that when applying the private creditor test, the risks related to previously granted aid schemes should not be taken into consideration during the assessment of a new measure. The purpose of this Insight is to clarify the limits of the private creditor test in a bank-bail-out scenario and provide further elements that confirm the Court's reasoning.